Examining the nonlinear effects of multidimensional land use efficiency on ecological resilience using the XGBoost-SHAP and GTWR model in Guangdong province - Liang, Tian; Zhan, Jinrui; Su, Yongjun; Deng, Weifeng (Frontiers in Environmental Science, 2025)
Understanding the complex interactions between land use efficiency (LUE) and eco-logical resilience (ER) is essential for sustainable urban development. However, existing studies have predominantly examined land use change and environmental impacts in isolation, while the nonlinear dynamics, threshold effects, and spatial heterogeneity of the LUE–ER relationship remain insufficiently explored. Moreover, limited attention has been paid to the heterogeneous roles of different LUE types—agricultural, industrial, commercial, and ecological—despite their divergent production functions and environmental externalities. Using panel data from 21 cities in Guangdong Province (2014–2022), this study investigates the spatiotemporal dynamics and interaction mechanisms of LUE and ER through an integrated XGBoost–SHAP and GTWR approach. Results show a 16.1% decline in ER across the province, mainly due to rising ecological pressure, with higher ER in the north and lower levels in the south. While industrial, commercial, and ecological LUE all declined significantly, agricultural LUE showed an increasing trend. Nonlinear and threshold effects were evident across all LUE types: agricultural, industrial, and ecological LUE significantly reduced ER once thresholds were exceeded, whereas commercial LUE enhanced ER beyond its threshold. The effects of LUE on ER were further moderated by industrial structure, green innovation, population density, urbanization, infrastructure, and government intervention. GTWR results reveal pronounced spatial heterogeneity and temporal divergence. Agricultural and industrial LUE consistently exerted negative relationship—particularly in the Pearl River Delta and eastern Guangdong—while commercial LUE evolved into a positive driver in northern and western cities. Ecological LUE shifted from a positive to a negative relationship over time. By disentangling multidimensional LUE effects and uncovering nonlinear thresholds and spatiotemporal heterogeneity, this study advances understanding of the LUE–ER nexus and provides differentiated, threshold-sensitive governance strategies for balancing land use optimization with ecological integrity in rapidly urbanizing regions.